Prévenir et guérir dans l’entre-deux-guerres à Suresnes (Hauts-de-Seine) - Émeline Trion; Marie-Pierre Deguillaume (In Situ)
The industrialisation of the suburban communes immediately surrounding Paris, at the end of the nineteenth century, led to demographic upheavals which are particularly visible at Suresnes, in the present-day Hauts-de-Seine department. Working-class inhabitants crowded into dilapidated and insalubrious buildings in the former centre, whilst the upper parts of the town remained empty. In the years after the First World War, several factors contributed to the development of social and urban policies of considerable ambition. These factors include legislation, recently enacted, that encouraged town-planning initiatives, projects for the organisation and extension of ‘Greater Paris’, and the election of Henry Sellier as mayor of Suresnes. They led to the development of new neighbourhoods and the establishment of a series of facilities dedicated to hygiene and healthcare. The ambition, to offer hygiene to all, created a broad variety of new facilities, at the same time as housing within the garden city was equipped with modern comforts. The facilities were like the rear base of a vast social system from which doctors, child-care workers and visiting nurses could sally forth throughout the territory. Today, as nearly all the dwellings have been modernised, these avant-garde facilities have been rethought and transformed, and their vocation either enlarged or completely altered. The article proposes a new look at the medico-social facilities of the interwar period and examines some key examples to show how they have changed.